Stress, Physical Activity, and Resilience Resources: Tests of Direct and Moderation Effects in Young Adults - Lines, R.; Ducker, Kagan; Ntoumanis, Nikos; Thogersen-Ntoumani, Cecilie; Fletcher, D.; McGarry, S.; Gucciardi, Daniel (American Psychological Association, 2018)
Stress is an important consideration for understanding why individuals take part in limited or no physical activity (PA). The effects of stress on PA do not hold for everyone, so examinations of possible moderators that protect individuals from the harmful effects of stress are required. Aligned with a resilience framework, individual resources (e.g., hope and self-efficacy) may buffer the maladaptive effects of stress, such that people who have access to these resources in greater quantity may be more "resilient" to the deleterious effects of stress on PA. This study was designed to test this expectation. In total, 140 Australian undergraduate students (70.7% female, Mage = 21.68 ± 4.88) completed a multisection survey and provided a sample for hair cortisol concentration analysis using immunoassays. Main effects demonstrated primarily small and nonsignificant associations between perceived stress and hair cortisol concentration with different intensities of PA. Similar findings were observed between individual-level resilience resources and PA intensities, with the exception of hope (i.e., positive association with vigorous PA and negative association with sitting), self-efficacy (i.e., positive association with vigorous PA), and resilience (i.e., positive association with walking). Although certain individual-level resilience resources were perceived as beneficial for PA and sedentary time, the moderating role of resilience resources was not supported by the findings. The direct and moderating effects between stress, PA, and resilience resources require further testing using longitudinal designs in which stressful periods occur naturally (e.g., exams for students) or are experimentally manipulated.